SYSTEM OF VALUE STANDARDS IN SOCIETY REFLECTED THROUGH KOREAN - VIETNAMESE FOUR-ELEMENT IDIOMS: A CASE STUDY BASED ON THE SEMANTIC ASPECT - Nguyen, Thuy Duong (VNU Journal of Foreign Studies, 2024)
People together create society, exist and develop as a social entity. No one can live independently, out of social relationships. Social relations are the foundation of every person’s life. The system of value standards in society is formed mainly from the needs of social relationships. This paper focuses on analyzing the meanings of 175 Korean four-element idioms (compared with 100 Vietnamese four-element idioms) which reflect the system of value standards in society. By analyzing the meanings of idioms, comparing with the social contents which are related to written standards (law) and unwritten standards (moral standards: fairness, respect for morality, love for fellow human beings) through idioms, we identify and explain the similarities and differences in the societies of Vietnam and South Korea through the special linguistic units - four-element idioms.